When This Happens, You Want the Best Care: Players' Experiences of Barriers and Facilitators of the Immediate Management of Rugby-Related Acute Spinal Cord Injury. (November 2019) - Badenhorst, Marelise; Verhagen, Evert; Lambert, Mike; van Mechelen, Willem; Brown, James
Most contact sports, including rugby union, carry a risk of injury. Although acute spinal cord injuries (ASCIs) in rugby are rare, the consequences of such injuries are far-reaching. Optimal management of these injuries is challenging, and a detailed understanding of the different barriers and facilitators to optimal care is needed. In this study, we aimed to describe the perception of players, regarding factors related to the optimal immediate management of a catastrophic injury in a developing country with socioeconomic and health care inequities. The most frequently reported barriers were transportation delays after injury and admission to appropriate medical facilities. Other barriers included inadequate equipment, the quality of first aid care, and barriers within the acute hospital setting. Barriers were more prevalent in rural and lower socioeconomic areas. These findings are relevant for all rugby stakeholders and may help shape education, awareness, and future policy around the immediate management of ASCIs.